1997
DOI: 10.1021/jm960653j
|View full text |Cite
|
Sign up to set email alerts
|

1-(2-Alkanamidoethyl)-6-methoxyindole Derivatives:  A New Class of Potent Indole Melatonin Analogues

Abstract: A new series of indole melatonin analogues, bearing the amido ethyl side chain attached at the N-1 position of the indole nucleus, were synthesized and tested for their affinity for the melatonin receptor isolated from quail optic tecta in a series of in vitro ligand-binding experiments using 2-[125I]iodomelatonin as the labeled ligand. The biological activity was evaluated using two models: effects on the forskolin-stimulated cAMP accumulation in explants from quail optic tecta and evaluation of the GTP gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 35 publications
1
50
0
1
Order By: Relevance
“…Previous data indicated that the 5-methoxy group is a major determinant in the attachment of MLT to its receptors [18] and there is evidence that it can influence the intrinsic activity, even if there are a number of examples of agonists that do not have the methoxy group [22][23][24][25][26]. A more extensive investigation of the importance of the methoxy substituent for biological activity and selectivity toward human mt 1 and MT 2 receptors was investigated by deleting this group or by shifting it from C-5 to the other indole positions.…”
Section: Substituent Modification On the Indole Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data indicated that the 5-methoxy group is a major determinant in the attachment of MLT to its receptors [18] and there is evidence that it can influence the intrinsic activity, even if there are a number of examples of agonists that do not have the methoxy group [22][23][24][25][26]. A more extensive investigation of the importance of the methoxy substituent for biological activity and selectivity toward human mt 1 and MT 2 receptors was investigated by deleting this group or by shifting it from C-5 to the other indole positions.…”
Section: Substituent Modification On the Indole Nucleusmentioning
confidence: 99%
“…The acyl group influences the affinity and the nature of the compounds to behave as agonists, partial agonists or antagonists. N-acetylated compounds were full agonists (22)(23)(24) or partial agonists (19)(20)(21), whereas the N-cyclobutanecarbonylamino derivatives (25,26) …”
Section: Substituent Modification On the Indole Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] From a wider perspective, the results obtained in this work provide basic knowledge that can be used to understand local conformational features in many relevant methoxyindole-containing naturally occurring and synthetic biomolecules. [26][27][28][29][30] Also, the possibility of controlling the conformational distribution of 6MOI in matrices opens a window for exploiting its conformer-specific reactivity in condensed media (as opposite to the gas phase). In addition, this work also demonstrates in a very clear way that exposition of a conformationally flexible sample to the broadband FIG.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized different series of melatonin analogues, obtaining very potent derivatives, such as 2-bromomelatonin. 8,9,10,11 Starting from a series of conformationally constrained compounds, we proposed a pharmacophore model for agonists and a bioactive conformation for the natural ligand. 12 A 3D-QSAR CoMFA analysis allowed the rationalization of the structure-activity relationships for more than one hundred agonists.…”
Section: Resultsmentioning
confidence: 99%